2019
DOI: 10.18203/2320-6012.ijrms20195015
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of the normal size of spleen and spleen to left kidney ratio among sudanese children up to five years age using ultrasonography

Abstract: Background: Knowledge of the normal range of spleen size in the population being examined is very important because there are many different pathological conditions that may alter in spleen size. Also, gender, height, weight and BMI of individual, affect the splenic length and could result in incorrect interpretation of splenic measurements, spleen to left kidney ratio is one of recent parameter mention in literature aid in diagnosis of splenomegaly in children.Methods: The study was a cross-sectional study co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Some investigators establish an internal reference for spleen size. This method adopted by [9] and [10] who found that the spleen to left kidney ratio was constant for all children age groups with a mean value of 1 and proposed a ratio of 1.3 as the upper limit for normal pediatric population. In our study the spleen to left kidney ratio is constant at around 1.1 for all ages, using 0.2 standard deviations above the mean as a guide, the upper limit of normal for the spleen to left kidney ratio is 1.3.…”
Section: Discussionmentioning
confidence: 99%
“…Some investigators establish an internal reference for spleen size. This method adopted by [9] and [10] who found that the spleen to left kidney ratio was constant for all children age groups with a mean value of 1 and proposed a ratio of 1.3 as the upper limit for normal pediatric population. In our study the spleen to left kidney ratio is constant at around 1.1 for all ages, using 0.2 standard deviations above the mean as a guide, the upper limit of normal for the spleen to left kidney ratio is 1.3.…”
Section: Discussionmentioning
confidence: 99%